Synthesis of an oxygenated fuel additive from a waste biomass derived aldehyde using a green catalyst: an experimental and DFT study. Issue 6 (9th April 2020) - Kumar, Komal; Khatri, Vikas; Parveen, Firdaus; Kashyap, Hemant K.; Upadhyayula, Sreedevi
Abstract : Herein, we report greener and sustainable synthesis of a green fuel additive using protic ionic liquid (PIL) catalysts from biomass derived 5-HMF and 1, 3-propanediol. Abstract : Herein, we report greener and sustainable synthesis of a green fuel additive using protic ionic liquid (PIL) catalysts from biomass derived 5-HMF and 1, 3-propanediol. The synthesized PIL catalysts were characterized using spectroscopic techniques such as 1 H NMR, 13 C NMR, and UV-visible spectroscopy. PIL catalyst [IL-SO3 H][CF3 SO3 ] gave a 99.2% 5-HMF conversion and 86.8% yield of the 5-HMF cyclic acetal in 2.5 h. The time, temperature, and molar ratio of the reactants for the 5-HMF conversion were optimized with the most active catalyst. Further, theoretical DFT calculations were performed for the PIL catalyst to calculate ion-pair interaction energies which revealed the activity of the catalyst. From DFT calculations, the interaction and dissociation energies of the ion-pairs of the PILs were determined. Further, the values of the chemical potential ( μ ) and chemical hardness ( η ) of the PILs were investigated using DFT. The experimentally determined Hammett acidity values of the catalysts were found to be in good agreement with the theoretical DFT study.